Conservação de bio-recursos algais no Brasil: estabelecimento de um banco criopreservado - Tessarolli, Letícia Piton (Universidade Federal de São Carlos, 2016)
The establishment of culture collections is a vital aspect for the conservation freshwater microalgae, which are a very diverse group of organisms with important ecological functions on the ecosystems maintenance and an immense although still sparsely explored biotechnological potential, particularly for the use of metabolites and biodiesel production. The traditional protocol for culture maintenance is the serial subculturing of metabollicaly active cultures. Although strains have been maintained in metabolically active cultures for decades, there are several reports of loss of characteristics for the organisms thus maintained, and an increase in the number of strains could be the cause for logistical challenges on the maintenance regimes and elevated costs with material and functionalism. Cryopreservation, which is the maintenance of organisms at ultra-low temperatures to the point that all cellular metabolic functions are paused, appears as a recommended alternative for the maintenance of long-term culture collections. The use of this technique allows the maintenance of samples for long periods of time with minimal handling, severely reducing the maintenance costs, while maintaining the stability of cultures, which should be stored at ultra-low temperatures to eliminate the occurrence of intracellular chemical processes. The Freshwater Microalgae Culture Collection (CCMA-UFSCar) currently maintains approximately 700 microalgae strains in metabolically active cultures, which is reaching maximum support capacity for routine maintenance practices. The requirements with cultures maintenance will also, consequently, affect the provision services of the collection, which are the basis of research of a large number of projects throughout Brazil. Thus, the main objective of this project was to test the feasibility of the use of cryopreservation as a technique to maintain algal cultures in this culture collection. For this, initially positive results were obtained for the application of a standard freezing protocol, particularly for green coccoid algae. However, larger and more complex organisms are still recalcitrant to freezing, with low rates of recovery, which will require further research and adaptation of the protocols to meet the particularities of each strain. In parallel to the establishment of the cryopreserved biobank for CCMA-UFSCar, projects were developed in order to further clarify details and consequences of the process of freezing and storing organisms at low temperatures, seeking to improve the success rates for the implementation of this technique. The effects of the presence of contaminating organisms on the microalgae cultures on the response of strains to freezing, and consequently on the formation of viable and robust post-thaw cultures, were verified a few selected non-axenic strains. It was noticed that the choice of cryoprotectant solution (CPA), used to protect cells during freezing, may be crucial for post-thaw recovery, and it is necessary to search for balance between obtaining the highest possible viability levels and avoiding the extreme proliferation of contaminating organisms, which could lead to inhibition in the recovery and quality of the desired algal cultures after the process. In addition to direct survival to the freezing process, which is a potentially damaging for cells, the longevity of samples maintained at different temperatures was also tested, aiming to establish the simplest and most cost-effective procedure to ensure the long term survival of frozen samples. It was observed that the storage temperatures, as well as the CPA used during freezing, were significant aspects to guarantee the continued viability of the frozen cultures, and only samples maintained immersed in liquid nitrogen were sufficiently protected against temperature fluctuations, ensuring the survival of all the samples for longer periods. Furthermore, the continuity of the viability for samples maintained immersed in liquid nitrogen was also observed in a study with samples maintained on these conditions for up to 40 years at Culture Collection of Algae and Protozoa (CCAP, UK). The freezing process per se is potentially damaging to the cultures during the process, which might be the cause for functional and genetic differences in cells that have undergone this process. Thus, biochemical and genetic analysis were used to verify the stability of the cultures submitted to the freezing protocol. To ensure the successful implementation of a cryopreserved microalgae bank for CCMA-UFSCar, in addition to viability and stability measures, it is necessary to establish protocols for sample management and routine maintenance. Thus, a case study was carried out with the experiences acquired in CCAP during the 40 years of the history of a cryopreserved bank, and how the application of these techniques can benefit the quality control and management of CCMA-UFSCar, facilitating the implementation of the cryopreserved biobank for this culture collection.
Keywords: Conservação da natureza; Algas de água doce; Nature conservation; Freshwater algae; CIENCIAS BIOLOGICAS::ECOLOGIA